A pedagogia na minha vida: relatos e reflexões de uma jornada de formação - Seixas, Maria do Socorro Gonzaga (Brasil, 2024)
The present academic work aims to report my academic trajectory during the Pedagogy course at the Federal University of Amazonas, offered by PARFOR, such as the challenges during the course, entry into the school as a student and teacher. Academic training at a higher level, reflection on teaching practice, supervised internships in Early Childhood Education, Early Years of Elementary School I and school management are also discussed.